The Knowledge and Attitude Related to Community Business Management - Wuttichai Sahattecho; Jirapa Junbua; Orawan Pairodwootthipong; Punsaporn Cruawong; Pattanaphanu Tooltham (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Community business is an essential alternative for local occupation. An excellent business manager requires knowledge and good attitude in order for their community business to become successful. This research is a descriptive research which aims to study the knowledge and the attitude of the participants in the community business management lecture in Tha Pho Community, Phitsanulok, Thailand, with 50 participants as the samples. The study results revealed that after the lecture, knowledge of the participants regarding community business management was at high level (92.50 percent). Similarly, the attitude on community business management was at high level (67.50 percent). Therefore, providing knowledge and attitude regarding community business management is important, so that entrepreneurs can truly understand community business management and strategy, which are essential for the success